2011
DOI: 10.1073/pnas.1104533108
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloid-specific estrogen receptor α deficiency impairs metabolic homeostasis and accelerates atherosclerotic lesion development

Abstract: ERα is expressed in macrophages and other immune cells known to exert dramatic effects on glucose homeostasis. We investigated the impact of ERα expression on macrophage function to determine whether hematopoietic or myeloid-specific ERα deletion manifests obesity-induced insulin resistance in mice. Indeed, altered plasma adipokine and cytokine levels, glucose intolerance, insulin resistance, and increased adipose tissue mass were observed in animals harboring a hematopoietic or myeloid-specific deletion of ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
138
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 59 publications
13
138
1
1
Order By: Relevance
“…3H) (D'Eon et al 2005), while teneligliptin suppressed the expression of Lpl, but did not affect that of Pparg or Fas in OVX-HF. On the other hand, a previous study with myeloid-specific ERa knockout mice demonstrated that estrogen attenuated chronic inflammation by directly inhibiting inflammatory responses by macrophages (Ribas et al 2011). In the present study, teneligliptin effectively attenuated chronic inflammation in the adipose tissue.…”
Section: Dpp4 Inhibitors Represent a Relatively New Class Of Antidiabsupporting
confidence: 50%
See 1 more Smart Citation
“…3H) (D'Eon et al 2005), while teneligliptin suppressed the expression of Lpl, but did not affect that of Pparg or Fas in OVX-HF. On the other hand, a previous study with myeloid-specific ERa knockout mice demonstrated that estrogen attenuated chronic inflammation by directly inhibiting inflammatory responses by macrophages (Ribas et al 2011). In the present study, teneligliptin effectively attenuated chronic inflammation in the adipose tissue.…”
Section: Dpp4 Inhibitors Represent a Relatively New Class Of Antidiabsupporting
confidence: 50%
“…It also reportedly enhances cholesterol uptake and suppresses gluconeogenesis in the liver (Bryzgalova et al 2006). Furthermore, estrogen was shown to attenuate obesity-induced chronic inflammation in adipose tissue by repressing the inflammatory responses of macrophages (Ribas et al 2011). Previous studies reported that estrogen acted on the CNS, especially on the hypothalamus, suppressing food consumption and increasing energy expenditure, thereby protecting against body weight gain (Xu et al 2011, Yonezawa et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transplant arteriosclerosis in rats or rabbits as well as macrophage infiltration into the allograft intima were potently reduced in E 2 -treated recipients, and this was associated with almost complete suppression of MHC-II antigen expression in transplanted arteries (Lou et al 1996, Saito et al 1998. Most recently, ERa-deficient macrophages were found refractory to IL4-induced activation of anti-inflammatory phenotype in vitro and presented with elevated expression of chemokines and markers of immune cell activity, when isolated from animals with myeloid-specific ERa deficiency (Ribas et al 2011). Importantly, Ldlr KO animals lacking ERa in myeloid cells showed twofold increase in atherosclerotic lesion area.…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 90%
“…In addition, E 2 was reported to reduce macrophage uptake of modified LDLs such as acetylated, oxidized, or aggregated LDL, and this latter effect was found to specifically depend on the ERa-mediated suppression of the expression of scavenger receptor CD36 (Sulistiyani & St Clair 1997, McCrohon et al 1999, Allred et al 2006, Wilson et al 2008. More recently, ERa-deficient macrophages were shown to express reduced amounts of proteins involved in cholesterol efflux such as ABCA1 and APOE and to export less cholesterol when incubated with HDL, whereas E 2 associated with HDL particles was found to potentiate HDL-induced cholesterol efflux mediated by scavenger receptor class B type I (SR-BI (SCARB1)) (Badeau et al 2009, Ribas et al 2011. Several studies documented that HDL carries E 2 in the form of fatty acyl esters produced in a reaction catalyzed by lecithin-cholesterol acyltransferase (LCAT; Helisten et al 2001, Höckerstedt et al 2002.…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 99%
“…Epidemiological studies suggest that estrogen protects women against CVD before menopause (2), and numerous animal studies have shown that estrogen significantly protects against the development of atherosclerosis (3)(4)(5). However, randomized controlled trials of postmenopausal estrogen therapy have demonstrated mixed CVD effects (6,7).…”
Section: Introductionmentioning
confidence: 99%